Use of scattering layer as a programmable spectrum filter - Wan L.; Ji X.; Singh R.K.; Chen Z.; Pu J. (My University, 2025)
Inhomogeneous and random scattering in a static-scattering medium diffuses an incident light field into a complex speckle pattern. This phenomenon leads to uncontrolled and unpredictable changes in the spectrum as incident polychromatic light is scattered by the static-scattering medium. In this paper, we propose and demonstrate a novel technique for shaping the randomly scattered spectrum into a controlled mode. The proposed technique is demonstrated experimentally by examples of bandpass spectrum, stairs, right triangle, and Gaussian spectra. A theoretical model for simulating polychromatic light field passing through a scattering medium is also developed. Theoretical and experimental results are consistent. The findings of this paper may present exciting applications, such as compensation for fiber dispersion. © 2019 IEEE